All Days 1997
DOI: 10.2118/37287-ms
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Impairment due to Asphaltenes During Gas Miscible Flooding and its Mitigation

Abstract: Introduction During miscible flooding of oil reservoirs by light hydrocarbon gases, deposition of asphaltenes inside reservoirs, and injection and production wells, can cause severe problems thereby adversely affecting the economics of oil recovery. In spite of this, very limited information regarding the asphaltene adsorption/deposition within porous media during gas miscible flooding, is available. In the present work, the flow of oil-solvent mixtures through porous media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Because of the impact of asphaltene aggregation during gas injection, several studies have been conducted focusing on cyclic gas injection in conventional reservoir cores. Others investigated the stability of asphaltene under carbon dioxide (CO 2 ) gas injection and different factors were studied. CO 2 can evaporate more hydrocarbon components and condensate at a higher concentration into crude oil than N 2 , resulting in more asphaltene depositions . There have been very little studies employing N 2 gas injection to illustrate the severity of asphaltene deposition and precipitation as well as the factors influencing its stability. Jamaluddin et al examined the asphaltene stability by contacting various molar concentrations of N 2 with the reservoir fluids and the findings revealed that increasing the concentration of N 2 negatively impacted the instability of asphaltene and increased the quantity of bulk precipitated asphaltene.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the impact of asphaltene aggregation during gas injection, several studies have been conducted focusing on cyclic gas injection in conventional reservoir cores. Others investigated the stability of asphaltene under carbon dioxide (CO 2 ) gas injection and different factors were studied. CO 2 can evaporate more hydrocarbon components and condensate at a higher concentration into crude oil than N 2 , resulting in more asphaltene depositions . There have been very little studies employing N 2 gas injection to illustrate the severity of asphaltene deposition and precipitation as well as the factors influencing its stability. Jamaluddin et al examined the asphaltene stability by contacting various molar concentrations of N 2 with the reservoir fluids and the findings revealed that increasing the concentration of N 2 negatively impacted the instability of asphaltene and increased the quantity of bulk precipitated asphaltene.…”
Section: Introductionmentioning
confidence: 99%